A leitura lacaniana do conceito freudiano de pulsão - Almeida, Henrique Batista (2016)
This thesis aims at investigating Jacques Lacan’s reading of the concept of instinct as defined by Sigmund Freud. This study started from the comprehension of the instinct theory in Freud’s work,investigating fundamental concepts related to the subject studied. In Lacan, the privileged concepts were the graph of desire and seminars of book 7: the ethics of psychoanalysis, and book 11: the four fundamental concepts. In the course of this study, there was the verification of Freud’s historical development of the concept expressed by the two instinctual dualisms: self drives (selfpreservation)/ sexual drives and life drive and death drive. Lacan promotes a resumption of Freudian text in a radical intricacy with the theory of language, which implies a new reading of the instinct theory.